2006
DOI: 10.1103/physrevlett.97.247201
|View full text |Cite
|
Sign up to set email alerts
|

First-Order Phase Transition in Easy-Plane Quantum Antiferromagnets

Abstract: Quantum phase transitions in Mott insulators do not fit easily into the Landau-Ginzburg-Wilson paradigm. A recently proposed alternative to it is the so-called deconfined quantum criticality scenario, providing a new paradigm for quantum phase transitions. In this context it has recently been proposed that a second-order phase transition would occur in a two-dimensional spin 1/2 quantum antiferromagnet in the deep easy-plane limit. A check of this conjecture is important for understanding the phase structure o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
68
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 28 publications
6
68
0
Order By: Relevance
“…A self-duality in the field theory suggested that this could be the best candidate for a deconfined critical point [5]. Subsequent numerical work has concluded however that this transition is first order, both in direct discretizations of the field theory [6,7] as well as in simulations of the quantum anti-ferromagnet [8]. The easy-plane case is in contrast to the symmetric SU(N ) case (we refer to this as s-SU(N )), where striking agreement between technical field theoretic calculations [9][10][11][12] and numerical simulations of the quantum magnets has been demonstrated [13][14][15].…”
mentioning
confidence: 99%
“…A self-duality in the field theory suggested that this could be the best candidate for a deconfined critical point [5]. Subsequent numerical work has concluded however that this transition is first order, both in direct discretizations of the field theory [6,7] as well as in simulations of the quantum anti-ferromagnet [8]. The easy-plane case is in contrast to the symmetric SU(N ) case (we refer to this as s-SU(N )), where striking agreement between technical field theoretic calculations [9][10][11][12] and numerical simulations of the quantum magnets has been demonstrated [13][14][15].…”
mentioning
confidence: 99%
“…This causes the N -component model without Josephson interactions to have N − 1 superfluid phase transitions and a single superconducting phase transition 17 . For certain values of the gauge charge these transitions will interfere in a non-trivial way, causing the transitions to merge in a single first-order transition 18,19 . The question of the nature of the phase transitions present in Josephson-coupled multiband superconductors is of considerable interest.…”
Section: Introductionmentioning
confidence: 99%
“…This regime corresponds to a large v 0 such that |z 1 | 2 ≈ |z 2 | 2 . However, recent Monte Carlo simulations [6,7] performed in this regime showed that the transition is actually (weakly) first-order.…”
mentioning
confidence: 96%
“…From the three models considered, only the one associated with an easy-plane antiferromagnet does not exhibit any second-order phase transition, in agreement with the numerical results of Refs. [6] and [7]. Deconfined spinons were shown to govern a second-order phase transition for both the isotropic SU (N ) antiferromagnet and quantum spin nematic systems.…”
mentioning
confidence: 99%
See 1 more Smart Citation